Pilgrimage Tourism Networks in Nepal: Prospects, Challenges, and Implications for Site-Based Economic Contribution Studies - Bhatt, Shankar Datt; Dwivedi , Ruchi (Journal of Research in Education, 2025)
Pilgrimage tourism shows one of the most consistent sources of travel demand of tourism. It is also crucial source of livelihood among rare heritage destinations in Nepal. As per the government tourism statistics throughout the post COVID recovery indicate that the proportion of visitors travelling for religious purposes raised in 2024 than 2023. Emphasizing the importance of religious travel in the Nepalese tourism economy. There has been limited research attention paid to understanding the linkages between pilgrimage tourism networks and their economic outcomes in major sacred sites. This study inspects the structure and economic impacts of pilgrimage tourism networks in Nepal using the Pashupatinath Sacred Site as a case study. Qualitative research approach that was based on secondary data. A conceptual economic contribution approach was used in analyzing the economic activities associated with pilgrimage sites. The significant economic benefits offered by pilgrimage tourism through ritual consumption (offerings and puja services), accommodation, food services, transportation, retail trade, informal employment, and site-area services. The expenditures and small scale service activities were identified as the most consistent sources of local income. Further, research provides a site-based measurement framework that can be used in future research with visitor expenditure surveys, vendor profiling, and multiplier analysis to estimate the total economic contribution of pilgrimage tourism. The study points out major policy implications, including improved visitor management and service quality, improved local value capture through local procurement, support for smaller enterprises through transparent licensing and zoning systems, also institutionalization of destination data systems for planning and monitoring.